Modelling fiber drawing: Capillary manufacture - Fitt, A; Please, C; Furusawa, K; Monro, T (2002)
Fiber drawing for capillary manufacture was presented. Microstructured fibers were produced by drawing a macroscopic preform into fiber using a drawing tower. The degree of hole closure was controlled by introducing a pressure difference between air inside and outside the capillary.